SATIRE KEPADA PENGUASA DALAM LIRIK LAGU TIKUS-TIKUS KANTOR KARYA IWAN FALS - Eny Widianti; Wisnu Putri Febriani; Sri Wahono Saptomo (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
Language plays a very important role in human life because without language, interaction between people will be hampered. Language has a style, the language style in literary works functions, among other things, to obtain maximum meaning, namely clearer and more lively, to create a certain atmosphere and impression in the reader's heart, and to obtain aesthetic effects. The method used in this study is a qualitative descriptive method. Data collection was carried out by playing a song titled Tikus-tikus Kantor, listening to the lyrics carefully, and recording the lyrics of the song. The technique used to analyze the lyrics of the song Tikus-tikus Kantor by Iwan Fals is content analysis. Based on the results of the research, the style of satirical language was found in the first, second, third, fifth, and sixth stanzas of each lyric. The satire is in the form of a satire of officials who like to commit corruption and act as if they did not commit a crime during the examination. In this case, the law enforcement officials do not seem to care and the public considers the performance of the law enforcement officials to be bad because they cannot eradicate corruption committed by corruptors.